A case of longstanding primary sclerosing cholangitis. Issue 11 (November 1983) - Goudie, B M; Birnie, G G; Watkinson, G; MacSween, R N
Abstract : A 45-year-old man is described in whom there is currently ERCP and histological evidence of primary sclerosing cholangitis (PSC). A liver biopsy obtained 29 years ago shows similar histological features confirming that he had PSC at that time. This case indicates that PSC may follow a relatively benign course.